1880. Detection of Infectious SARS-CoV-2 in Specimens with High CT Values Is More Common for Omicron than for Delta Variants. (15th December 2022) - Tassetto, Michel; Garcia-Knight, Miguel; Anglin, Khamal; Kelly, Dan; Lu, Scott; Pineda-Ramirez, Jesus; Saydah, Sharon; Briggs-Hagen, Melissa; Zhang, Amethyst; Sanchez, Ruth Diaz; Donohue, Kevin; Romero, Mariela; et al.
Abstract: Background: Although not validated, cycle threshold (Ct) values from real-time (r)RT-PCR are sometimes used as a proxy for infectiousness to inform public health decision-making. A better understanding of variant-specific viral dynamics, including RNA and infectious virus relationships, is needed to clarify implications for diagnostics and transmission. Methods: Non-hospitalized SARS-CoV-2-infected individuals were recruited ≤ 5 days post-onset and self-collected nasal swabs daily for two weeks. Sequencing was used to determine variant, an in-house quantitative rRT-PCR targeting N gene was used to produce Ct values and determine RNA load, and cytopathic effect was used to assess the presence or absence of infectious virus (binary outcome). We used a Ct threshold of 30 to define high-Ct (Ct > 30) or low-Ct (Ct ≤ 30) specimens and assessed the percentage of RNA-positive specimens that had infectious virus; variant-specific percentages were compared by Χ 2 test. Results: We included 113 and 200 RNA-positive specimens from 18 and 28 Omicron- and Delta-infected participants, respectively; timing of RNA-positive specimen collection was similar in both groups (median = 8d post-onset). Maximum observed RNA levels occurred at median of 5 days post-onset for both variants but were lower for participants with Omicron vs Delta [mean RNA copies/mL = 10 5.2 vs 10 7.9 ]. Despite lower RNA levels, infectious virus was frequently detected for both variants [Omicron: median duration = 4.5d; Delta: median = 6d; p = 0.13]. Omicron specimens with infectious virus had higher Cts vs Delta specimens [mean Ct = 29.9 vs 23.2, p < 0.001]. In high-Ct specimens (Ct > 30; Table ), the percentage of specimens with infectious virus was typically higher for Omicron vs Delta, and was significantly higher in adults [27.3% vs 9.5%]. In low-Ct specimens (Ct ≤ 30), the percentage with infectious virus was similar or higher for Omicron vs Delta, and was significantly higher in children [87.5% vs 53.8%] and in those unvaccinated [94.1% vs 47.4%]. Conclusion: CDC does not recommend the use of Ct values as a proxy for infectiousness. These data further highlight that Ct values may not provide a reliable or consistent proxy for infectiousness across variants. Disclosures: All Authors : No reported disclosures.